Relationship-based marketing and its influence on customer loyalty in a commercial company, Bellavista, 2022 - Montero-Chumpitaz, Diana Briggiht; Fernandez-Bedoya, Victor Hugo (LACCEI, 2023)
The objective of this research was to determine the influence of relationship-based marketing on customer loyalty (and its dimensions: loyalty heart, information, internal marketing, communication, customer experience management and incentives and privileges) of a commercial company, Bellavista, 2022. The methodology had a quantitative approach, applied type, explanatory and descriptive level, non-experimental and cross-sectional design. The population consisted of 100 consumers of the company (finite). The study sample consisted of 80 customers. The technique applied was the survey. The instrument consisted of 18 items, which was submitted to 3 expert judges (Aiken’s V coefficient of 1.00). The reliability results were 0.923 Cronbach’s alpha overall and 0.830 Guttman’s two halves. It was concluded that relationship-based marketing significantly influences customer loyalty of a commercial company, Bellavista 2022 (sig.=0.000; r2=0. 3398) as well as in its dimensions heart of loyalty, information, internal marketing, communication, customer experience management and incentives and privileges (sig.=0.000, r2=0.3588; sig.=0.008, r2=0.0852; sig.=0.000, r2=0.1451; sig.=0.000, r2=0.2926; sig.=0.000, r2=0.3080; sig.=0.000, r2=0.2735) respectively. Finally, conclusions and recommendations were issued